Major Depressive Disorder Associated With Reduced Cortical Thickness in Women With Temporal Lobe Epilepsy - Nogueira, Mateus Henrique; Pimentel da Silva, Luciana Ramalho; Vasques Moreira, José Carlos; Rezende, Thiago Junqueira Ribeiro de; Zanão, Tamires Araújo; Campos, Brunno Machado de; Yasuda, Clarissa Lin; Cendes, Fernando (Frontiers in Neurology, 2020)
Background: Major Depressive Disorder (MDD) is highly prevalent in patients with mesial temporal lobe epilepsy (MTLE), especially in women, carrying significant morbidity. This study aimed to investigate the cortical thickness (CT) abnormalities associated with MDD in women with MTLE and hippocampal atrophy (HA). Also, we investigated the impact of MDD upon the volumes of the hippocampus and amygdala in these patients. Methods: We included 50 women with MTLE and HA (20 left, LMTLE; 30 right, RMTLE), 41 healthy women in the control group, and 15 women with MDD without epilepsy. MTLE patients were subdivided into three groups: MTLE-without-MDD (23 MTLE patients without MDD), MTLE-mild-MDD (nine MTLE patients with mild symptoms of MDD), and MTLE-severe-MDD (18 MTLE patients with moderate to severe symptoms of MDD). The five groups were balanced for age (p=0.56). All participants had high-resolution 3D T1-weighted images in a 3T scanner. We used FreeSurfer6.0 for volumetry and CT parcellation. All participants were submitted to a clinical psychological evaluation through the Structured Clinical Interview for DSM-IV (SCID-IV) and completed the Beck Depression Inventory (BDI-II). Results: We identified a smaller ipsilateral amygdala volume (p=0.04) in the MTLE-severe-MDD group when compared to the control group. Our results presented a reduced ipsilateral lateral orbitofrontal cortex (p=0.02) in the MTLE-severe-MDD in comparison to the MTLE-mild-MDD group. We also identified a thinner ipsilateral fusiform gyrus (p<0.01) in the MTLE-severe-MDD compared to both MTLE-without-MDD and control groups. A reduced CT of the contralateral superior frontal gyrus (p=0.02) was observed in the MTLE-severe-MDD in comparison to the MTLE-mild-MDD group. Conclusions: The identification of areas with reduced CT and atrophy of the ipsilateral amygdala in women with MTLE and MDD suggest that the cortical thinning in the network of the paralimbic system related to the co-occurrence and intensity of depressive symptoms in this group.